Toward Defining and Measuring the Fiscal Impact of Public Enterprises. (IMF Working Papers; Working Paper, 1989)
In many countries, the activities of public enterprises have an important fiscal impact. While the precise nature of this impact is often obscured, it is important that it be reflected in measures of overall fiscal activity. The paper is intended to raise and clarify some of the issues involved in this task.